2014
DOI: 10.1098/rsbl.2014.0439
|View full text |Cite
|
Sign up to set email alerts
|

Video demonstrations seed alternative problem-solving techniques in wild common marmosets

Abstract: Studies of social learning and tradition formation under field conditions have recently gained momentum, but suffer from the limited control of socio-ecological factors thought to be responsible for transmission patterns. The use of artificial visual stimuli is a potentially powerful tool to overcome some of these problems. Here, in a field experiment, we used video images of unfamiliar conspecifics performing virtual demonstrations of foraging techniques. We tested 12 family groups of wild common marmosets. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 15 publications
0
51
1
Order By: Relevance
“…Studies of multiple groups of wild primates within single populations have demonstrated social learning through field experiments (in four groups of lemurs, Schnoell & Fichtel, ; in up to 13 groups of marmosets, Gunhold, Massen, Schiel, Souto, & Bugnyar, ; Gunhold Whiten, & Bugnyar, ; in up to six groups of vervet monkeys, van de Waal et al, ; van de Waal et al, ; van de Waal, Borgeaud, et al, ; de Waal et al, ; de Waal, Claidière, & Whiten, ; van de Waal & Bshary, ). However, long‐term observations of these populations, with the aim of revealing potential intergroup differences, are to my knowledge lacking, until this present review of behavioural variation in wild vervet monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of multiple groups of wild primates within single populations have demonstrated social learning through field experiments (in four groups of lemurs, Schnoell & Fichtel, ; in up to 13 groups of marmosets, Gunhold, Massen, Schiel, Souto, & Bugnyar, ; Gunhold Whiten, & Bugnyar, ; in up to six groups of vervet monkeys, van de Waal et al, ; van de Waal et al, ; van de Waal, Borgeaud, et al, ; de Waal et al, ; de Waal, Claidière, & Whiten, ; van de Waal & Bshary, ). However, long‐term observations of these populations, with the aim of revealing potential intergroup differences, are to my knowledge lacking, until this present review of behavioural variation in wild vervet monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…This automation process has continued ever since, now reaching the stage of entirely automated phenotyping for dozens of cognitive, behavioural, and personality traits in laboratory rodents (Jhuang et al, 2010;Maroteaux et al, 2012). A number of automated devices have recently been developed for cognitive tests in captivity (Fagot & Bonté, 2010;Steurer, Aust & Huber, 2012) or in the wild (Ohashi, D'Souza & Thomson, 2010;Nachev & Winter, 2012;Gunhold, Whiten & Bugnyar, 2014). These data could be combined with video analysis of behaviour at the device (e.g.…”
Section: (B) Technological Innovationsmentioning
confidence: 99%
“…T&M argue we should look at evidence for social learning from the wild. Evidence for social learning in callitrichids in the wild is clearly available, and by no means restricted to parent‐offspring contexts (Gunhold, Whiten & Bugnyar, ; Gunhold et al ., ). However, even though establishing social learning experimentally in the wild is possible (Reader & Biro, ), not all species are equally amenable to field experiments, producing biases.…”
Section: Immediate Consequences: Proximate Mechanisms and Performancementioning
confidence: 99%